Penyuluhan Program Literasi Informasi Kesehatan dalam Meningkatkan Kualitas Sanitasi bagi Masyarakat di Kaki Gunung Burangrang Kab. Bandung Barat - Ditha Prasanti; Ikhsan Fuady (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
The ability of the community to access information needs is still uneven among urban people and rural communities. The ability to access information is an open door that must be open to be able to process and understand information, especially in this case is health information. Sanitation is one component of environmental health, a deliberate behavior to civilize a clean life to prevent humans directly touched with dirt and other hazardous waste materials, in the hope of maintaining and improving human health. Therefore, the authors perform Community Service activities entitled